Hyperthermic Intraperitoneal Chemotherapy with Melphalan: A Summary of Clinical and Pharmacological Data in 34 Patients. (3rd July 2012) - Bijelic, Lana; Sugarbaker, Paul H.; Stuart, O. Anthony
Abstract : Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is a treatment option for peritoneal metastases. The optimal agents for HIPEC have not been established. Melphalan is a drug with broad activity and a favorable profile for intraperitoneal application. The purpose of this study is to review our experience using melphalan for HIPEC. Pharmacologic data was obtained. Thirty four patients who underwent CRS for peritoneal metastases received melphalan for HIPEC between 2003 and 2011. The first 10 patients received 70 mg/m 2 ; subsequent 24 received 60 or 70 mg/m 2 . The mean PCI was 21 ± 7 . Twenty-eight patients (83%) had a CC score of 1 or 2. The mean length of stay was 18 ± 2 days. Nine patients (26%) had a grade 3 and 6 (17%) had grade 4 morbidity. There were no postoperative deaths. The pharmacologic analysis of plasma to peritoneal fluid levels of melphalan showed an AUC ratio of 33 while the tumor nodules to peritoneal ratio was 8. Melphalan is an acceptable agent for use in HIPEC. The morbidity of intraperitoneal melphalan at the dose of 60–70 mg/m 2 appears acceptable. Further studies comparing the effectiveness of melphalan and other HIPEC agents are needed.